If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8-2 (a+1)=9a
We simplify the equation to the form, which is simple to understand
8-2(a+1)=9a
Reorder the terms in parentheses
8+(-2a-2)=9a
Remove unnecessary parentheses
+8-2a-2=+9a
We move all terms containing a to the left and all other terms to the right.
-2a-9a=-8+2
We simplify left and right side of the equation.
-11a=-6
We divide both sides of the equation by -11 to get a.
a=0.545454545455
| 64qp^3-25pq^3=0 | | x^4-5x^2+10=0 | | 7(4x-2)=-42 | | x+3/4=x+5/6 | | 5x+30=15x-8 | | 7y-5x=61 | | 17-15=x/-8 | | 5x/6=5/21 | | -4(x+5)=-40 | | 3=7y | | -y+23=6y+2 | | 5x-8y=19 | | 4x=2-(-2) | | 4.9x^2-2.5x+53=0 | | 12n+2(n-3)=7+5(2n-1) | | 10=3+4 | | 6x-6=6(x-8) | | e^2=24 | | 10=re | | 2y+3/3=y+2 | | 12y=12y | | (9x-9)/3=x^2-9x-5 | | (2x^2-5x+4)/(x+1) | | 0=90000000000m | | 2456(x+23)=368400 | | 2456(x+23)=85960 | | 5e^2=120 | | 2x-3x/5=14 | | 8+2y=7 | | 1000=90000000000m | | 3c-1/2(c-14)=2 | | x^3-2x^2+x+6= |